Conditionnement d'une horloge de haute précision Leroy pour son transport et sa mise en réserve - Anaïs Vecten (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
A constant-pressure clock built by L. Leroy & Co. was mounted in the Observatory of Neuchâtel in 1949 for the transmission of time and was turned off in 1962. The clock is now conserved on site, currently disassembled in six constituents.  The clock contains some fragile assembling materials and is vulnerable to shocks. It is susceptible to mercury spills, and some of its constituents are heavy and bulky. A storage packaging as well as a demountable light transport case was designed to ensure its long-term conservation in accordance to these specific characteristics. All materials were selected by different tests and tools.